(3ebGdI CQTejOS aj JcSjQ GdOGFQIs - (3CQTejOSs
(3ChdgG (B:s
(3cd OGFQI agi eSGhjI deKdK bGFe GdRhGjI s
(3BNQgG (B:s
(3hgPG JeGe Gdbhd ai JcSjQ GdOGFQI s
(3Vef eLehY s
(3hQO CjVG eY cJGH (B: (3JMQjQ cJGH CQTejOS (B" (3JMJ Qbe (B" 31" (3QjGVjGJs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B88 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs